Perceived Risk and Mobile Shopping Motivations in Ilocos Norte Philippines - Eric S Parilla; Marc Edward M Abadilla (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
This study aims to determine the effect of perceived risk on mobile shopping motivations. It proposes how product risks and service risks affect mobile shopping motivations. It used a descriptive-correlation research design, and the respondents are Ilocos residents who used their mobile phones for shopping. Convenience sampling was used, and the research approach is quantitative. It used frequencies, weighted mean, and Pearson r to analyze the data. The study has implications for marketing management, such as for online shop owners and advertisers who intend to measure how to promote products on online platforms. The original contribution of this study lies within its questionnaire that has been attuned to the effects of perceived risks to mobile or online shopping motivations. The mobile shopping motivations of Ilocano buyers are efficient to use, easy and convenient to use, and the sense of enjoyment when shopping online. The relationship between product risk and mobile shopping motivation is established in this research. Implications were also discussed.